2018
DOI: 10.1128/mbio.00379-18
|View full text |Cite|
|
Sign up to set email alerts
|

The Escherichia coli Phospholipase PldA Regulates Outer Membrane Homeostasis via Lipid Signaling

Abstract: The outer membrane (OM) bilayer of Gram-negative bacteria is biologically unique in its asymmetrical organization of lipids, with an inner leaflet composed of glycerophospholipids (PLs) and a surface-exposed outer leaflet composed of lipopolysaccharide (LPS). This lipid organization is integral to the OM’s barrier properties. Perturbations of the outer leaflet by antimicrobial peptides or defects in LPS biosynthesis or transport to the OM cause a compensatory flipping of PLs to the outer leaflet. As a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 53 publications
4
75
0
Order By: Relevance
“…Conversely, in a ΔpldA background, the mlaA* dominant allele was no longer lethal in a stationary-phase phenotype (33). These findings, combined with recent work establishing a link between PldA byproducts as a feedback system to modify LPS levels (37), establishes PldA as a sensor of outer membrane asymmetry and playing an important role in cell-envelope maintenance.…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, in a ΔpldA background, the mlaA* dominant allele was no longer lethal in a stationary-phase phenotype (33). These findings, combined with recent work establishing a link between PldA byproducts as a feedback system to modify LPS levels (37), establishes PldA as a sensor of outer membrane asymmetry and playing an important role in cell-envelope maintenance.…”
Section: Discussionmentioning
confidence: 72%
“…mlaA* mutants aberrantly transport phospholipids to the outer leaflet of the OM, which normally comprises almost exclusively LPS (1,2). The accumulation of phospholipids in the outer leaflet triggers compensatory LPS synthesis via increased activity of LpxC, which ultimately destabilizes the OM and leads to vesiculation and loss of OM lipids (1,3,4). During growth, lost lipids can be replenished by ongoing synthesis and transport from the IM to the OM.…”
Section: Supplementary Textmentioning
confidence: 99%
“…Importantly, increased LpxC activity in mlaA* is believed to be caused by reduced FtsH proteolysis (1,3). Thus, deletion of ftsH in P. aeruginosa could compromise cell integrity by inducing LPS overproduction, phenocopying the results in E. coli.…”
Section: Supplementary Textmentioning
confidence: 99%
“…via the Mla pathway) or degradation (e.g. by PldA and PagP) (9)(10)(11)(12). Previous studies found that Escherichia coli strains with mutations in genes required for LPS biosynthesis or transport, such as lpxC (previously known as envA) (13) or lptD (also known as ostA or imp) (8), have permeability defects in their OM compared to their wild-type counterparts (14,15).…”
Section: Introductionmentioning
confidence: 99%